Analysis of the Effect of Contextual Problem Solving on Students’ Mathematical Reasoning Ability - Ahmad Basid; Eko Sutrisno; Lale Rahman Aliyeva (International Journal of Science and Mathematics Education, 2024)
This study investigates the impact of contextual problem-solving on students' mathematical reasoning abilities, comparing it to traditional problem-solving exercises. The study employs a quasi-experimental design with two groups: an experimental group exposed to contextual problem-solving activities and a control group using conventional methods. The experimental group demonstrated a 24% improvement in their mathematical reasoning abilities compared to the control group. Contextual problem-solving, which integrates real-world problems into the learning process, was found to be more engaging and effective in promoting deeper understanding and application of mathematical concepts. The study highlights the benefits of contextual learning in making abstract mathematical concepts more tangible and relatable to students. The findings suggest that by connecting mathematical knowledge to real-world scenarios, students develop stronger reasoning skills and improve their problem-solving capabilities. Moreover, the study recommends incorporating more contextual problem-solving exercises into curricula and providing teachers with training on how to implement these strategies effectively. It also suggests that future research explore the long-term effects of contextual problem-solving on other learning areas, such as critical thinking and creative problem-solving. This approach not only enhances students' mathematical reasoning but also fosters a more engaging and meaningful learning environment, thus preparing students to apply their mathematical knowledge in real-life situations.